Deciding What We See - Joe Courson (Journal of Applied Communications, 1986)
About six people will decide In a few minutes what hundreds of thousands of people like you and me will see on tonight's TV news. At most Georgia TV stations, the procedure for determining what stories are covered is about the same. Let's look at a day in WSB-TV's news operation in Atlanta.